Geographic Distribution of Authors Contributed to Applied Food Biotechnology (2014-2023) - Masoumeh Moslemi (Applied Food Biotechnology, 2023)
In this editorial article, nationality of the authors from establishment of Applied Food Biotechnology from 2014 to the present time has been overviewed. The editorial board, especially chief editor, wish to make a broad global audience to spread knowledge of food biotechnology via publication of outstanding articles in this journal. At the beginning of the activity of journal office, a limited number of non-Iranian authors submitted their manuscripts to this journal; however immediately after the publication of the first issue, number of the foreign authors increased further, while they showed their satisfaction with the acceleration in peer-review processes of their manuscripts. From the published articles, probiotics has been the major scope; therefore, screening of the beneficial probiotics from various natural sources and their uses in prevention of diseases have been introduced by various authors. Thus, the most interesting findings of the authors have been introduced; through which, readers are further adapted to the journal priorities and preferences in probiotics and postbiotics. It is believed that invitation of prestigious authors and carrying out rapid peer-review processes are a key success to achieve high article citations and authors’ satisfactions.